Determinasi Teori Fraud Hexagon dan Karakteristik Komite Audit dalam Mendeteksi Kecurangan Laporan Keuangan - Astri Hardirmaningrum; Abdul Rohman (Jurnal Akademi Akuntansi, 2023)
Purpose: This study aims to determine the influence of elements from the fraud hexagon theory and characteristics of audit committees on detecting financial statement fraud. Methodology/approach: The study data uses secondary data sourced from annual reports of manufacturing companies in the basic and chemical industry sebsectors listed on the IDX for 2019-2022 period. Findings: This study resulted in findings that pressure has a positive effect and opportunity has a negative effect on financial statement fraud. Rationalization, capability, arrogance, collusion and two characteristics of audit committee, namely financial expertise and frequency of audit committee meetings has no effect on financial statement fraud. Practical and Theoretical contribution/Originality: These findings contribute to researchers and business managers in increasing understanding of the factors that lead to fraud through the hexagon fraud model an characteristics of audit committees, so as to reduce frequency and amount of losses due to fraud. Novelty this study is to use the independent variable characteristics of audit committee, namely financial expertise and frequency of meetings on detecting financial statement fraud. Research Limitation: The independent variables in this study are only 31.6% which affect the detection of financial statement fraud. While the remaining 68.4% is influenced by other variables outside this research model. In addition, this study also cannot be generalized because only one sub-sector of the company is examined.